Al-Falah: sistem pengurusan rekod masjid / Siti Noor Azmawaty Abd Razak ...[et al.] - Abd Razak, Siti Noor Azmawaty; Yusoff, Ruslaina; Wan Mohamad, Wan Nurul Basirah; Abdul Rahman, Shariful Amran (Universiti Teknologi MARA Cawangan Kelantan, 2019)
Mosques are classified as not for profit organization that deal with public funds received mainly form government allocations, corporate bodies as well as public donations. Hence, the recording and bookkeeping is one of the crucial aspects to be considered, especially in handling funds received and disbursed by them. The fact that those handling the mosques‟ funds may not be financially literate posed a key challenge to an efficient and proper management of cash flows. Owing to that, the objective of Al-Falah is to assist these trustees of mosques funds in bookkeeping and recording their daily receipts and disbursements. Al-Falah is system that is simple to understand yet easy to operate among computer users. It can run under a moderate computer specification. The base was Microsoft Excel and it contains several key features of recording monthly receipts, disbursements and generating monthly report. At the month end, users will be able to determine the remaining funds to be brought forward to the next period. The added feature of auto generating a statement for the current month is an important record for auditing of funds by the governing body. Al-Falah is expected to solve some criticism for improper recording and reporting of receipts and disbursements of mosques. Henceforth, Al-Falah shall be updated, adding more useful features such as yearly recording to it and is expected to be used by every mosque in Kelantan